Observed Rate of Down Syndrome in Twin Pregnancies. Issue 5 (November 2016) - Sparks, Teresa N.; Norton, Mary E.; Flessel, Monica; Goldman, Sara; Currier, Robert J.
Abstract : OBJECTIVE: To evaluate the observed incidence of Down syndrome in twins compared with that expected based on maternal age–matched singletons, which is the current clinical approach. METHODS: This was a retrospective review of California Prenatal Screening Program participants with expected delivery dates between July 1995 and December 2012. Cases confirmed prenatally or postnatally with a genetic imbalance leading to phenotypic Down syndrome (trisomy 21, mosaic trisomy 21, or translocations) were included. Pregnancies conceived with ovum donation and women older than 45 years were excluded. We compared the observed Down syndrome incidence per pregnancy for twins with expected incidence by extrapolating from singleton data and expected zygosity as is the current clinical approach. This extrapolation assumes that monozygotic pregnancies have equivalent Down syndrome risk per pregnancy relative to maternal age–matched singletons and dizygotic pregnancies have twice the risk of at least one affected fetus. Zygosity for affected cases was presumed to be monozygotic with Down syndrome concordance and dizygotic with Down syndrome discordance. Counts were compared using cumulative Poisson distributions. RESULTS: Of 77, 279 twin pregnancies, 182 (0.2%) had at least one fetus with Down syndrome confirmed by karyotype. The ratio of observed-to-expected Down syndrome incidence per pregnancy was 33.6%, 75.2%, and 70.0% for monozygotic, dizygotic, and all twins, respectively ( P <.001 for all comparisons). Considering maternal age subgroups and twin zygosity, a significantly lower-than-expected Down syndrome incidence was seen for women aged 25 to 45 years with monozygotic pregnancies and overall for women aged 25 to 45 years with dizygotic pregnancies. CONCLUSION: The observed incidence of Down syndrome in twin pregnancies is lower than expected, most notably for monozygotic pregnancies and with increasing maternal age. Risk-based counseling can strongly affect women's choices regarding testing and management during pregnancy, so an understanding of the true Down syndrome risk in twin gestations is crucial. Abstract : Supplemental Digital Content is Available in the Text.The observed incidence of Down syndrome in twin pregnancies is lower than expected based on current models, particularly for monozygotic pregnancies and with increasing maternal age.